Incidence, Gleason Score and Ethnicity Pattern of Prostate Cancer in the Multi-ethnicity Country of Iran During 2008-2010 - Basiri, Abbas; Eshrati, Babak; Zarehoroki, Ali; Golshan, Shabnam; Shakhssalim, Nasser; Khoshdel, Alireza; Kashi, Amir Hossein (Urology Journal, 2020)
Purpose: To investigate the geographical incidence, and grade of prostate cancer in Iran during 2008-2010 and evaluate its relationship with ethnicity. Materials and Methods: Data was extracted from the nationwide Iranian cancer registry system during 2008-2010. Pathologies and grade was extracted from scanned reports of patients’ pathologies by a urologist. Results: The average 3-year age standardized incidence rate of prostate cancer during the study period was 11.52 per 100000 males. The age standardized incidence rates for Persian, Arab, Turkish and Turkmen, Lor, Kurd and Baluch ethnicities were 13.5, 9.3, 7.9, 7.9, 7.2 and 2.1 per 100000, respectively. Poisson regression analysis revealed a statistically significant difference in incidence of prostate cancer in Baluch ethnicity (P=0.028) and a near significant difference for incidence of prostate cancer in Turk-Turkmen and Kurd ethnicity (P=0.067 and P=0.082) in comparison with Persian ethnicity. The median Gleason score distribution of prostate cancer was not concordant to the age standardized incidence rates. 97% of all pathologies were adenocarcinoma of the prostate followed by malignant carcinoma (1.9%), and transitional cell carcinoma (1.1%). Conclusion: The incidence of Prostate cancer was different between Baluch and Fars ethnicities in Iran. The lowest ASR of PCa was observed in Baluch ethnicity, however the possibility of underreporting due to less access in Baluch ethnicity cannot be ruled out. The Gleason distribution pattern was not concordant to the incidence distribution of Prostate cancer.